Mycoplasma pneumoniae 23S rRNA A2063G mutation does not influence chest radiography features in children with pneumonia. Issue 1 (January 2018) - Deng, Huan; Rui, Jun; Zhao, Deyu; Liu, Feng
Objective: To measure the rate of the A2063G mutation in the Mycoplasma pneumoniae ( M. pneumoniae ) 23S rRNA domain V in children with pneumonia and to determine the correlation between radiographic findings and the presence of the A2063G mutation. Methods: Patients who were hospitalized with a confirmed diagnosis of M. pneumoniae pneumonia were enrolled in this study. M. pneumoniae strains were collected for genotype analysis. Chest radiography was performed on all children prior to and following macrolide treatment. Clinical and imaging data were obtained. Results: Of 211 patients, 195 (92.42%) harboured M. pneumoniae with the A2063G mutation. No significant differences were identified in inflammation score, chest radiography inflammation absorption grade before and after macrolide treatment, or pulmonary complications (atelectasis, hydrothorax, or pleuritis) prior to macrolide treatment when children were stratified based on the presence or absence of the A2063G mutation. Conclusions: A high proportion of children with pneumonia harboured strains of M. pneumoniae with the A2063G mutation in the 23S rRNA domain V. However, no obvious chest radiographic features of M. pneumoniae pneumonia were associated with the A2063G variant.